2015
DOI: 10.1371/journal.pone.0138575
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cochlear Implant Outcomes in Children with GJB2 and SLC26A4 Mutations

Abstract: ObjectivesTo investigate speech and language outcomes in children with cochlear implants (CIs) who had mutations in common deafness genes and to compare their performances with those without mutations.Study DesignProspective study.MethodsPatients who received CIs before 18 years of age and had used CIs for more than 3 years were enrolled in this study. All patients underwent mutation screening of three common deafness genes: GJB2, SLC26A4 and the mitochondrial 12S rRNA gene. The outcomes with CIs were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…Moreover, at 3 years after implantation, both homozygous and heterozygous children with mutated SLC26A4 alleles (n = 18 and n = 22 including heterozygotes) demonstrated a better CAP score than children with no detected mutation (n = 75) (Wu et al, 2011). Age is an essential factor in CI performance with this mutation, children older than 3.5 years had no significant differences in post CI performance compared to those without mutations (Wu C.-M. et al, 2015).…”
Section: Othermentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, at 3 years after implantation, both homozygous and heterozygous children with mutated SLC26A4 alleles (n = 18 and n = 22 including heterozygotes) demonstrated a better CAP score than children with no detected mutation (n = 75) (Wu et al, 2011). Age is an essential factor in CI performance with this mutation, children older than 3.5 years had no significant differences in post CI performance compared to those without mutations (Wu C.-M. et al, 2015).…”
Section: Othermentioning
confidence: 87%
“…Outer sulcus cells; regulates volume CI before 3.5 years of age, patients show significantly higher CAP/SIR scores than those without mutations 3 years post-implant (Wu C.-M. et al, 2015) At 3 years after implantation, both homozygous and heterozygous children (n = 18 and n = 22 including heterozygotes) had better CAP scores than children with no detected mutation (n = 75) (Wu et al, 2011) Limitations: Effects on CI outcomes may depend on the age of implantation, children older than 3.5 years had no significant differences in post CI performance compared to those without mutations (Wu C.-M. et al, 2015 (Eppsteiner et al, 2012;Usami et al, 2020) Limitations: The causes of the discordant outcomes further investigation.…”
Section: Slc26a4* Pendrinchloride−formate Exchangermentioning
confidence: 96%
See 1 more Smart Citation
“…Mutations in GJB2 have been shown in multiple studies to be associated with excellent CI outcomes . Similarly, good CI outcomes have been reported in individuals with other genetic lesions affecting the sensory apparatus including mutations in genes that affect the cells of the stria vascularis ( SLC26A4 ), the tip‐links of the stereocilia of the inner hair cells ( CDH23 ), the unconventional myosin motor proteins of the hair cells ( MYO7A ), and the stereocilia structure itself ( LOXHD1 ), among others. One large study of 173 individuals who underwent cochlear implantation showed that any mutation in a deafness‐causing gene affecting the organ of Corti was associated with good CI outcomes .…”
Section: Genetic Lesions To the Sensory (Cochlear) Partitionmentioning
confidence: 92%
“…Categories of auditory performance (CAP) and speech intelligibility rating (SIR) scores were assessed at 3 months, 6 months, 1 year, 3 years and 5 years post‐implant, whereas speech perception tests were performed at 3 years post‐implant . The duration of CI use in the 10 patients with OTOF mutations ranged from 1 to 7 year as of preparation of this article.…”
Section: Methodsmentioning
confidence: 99%